Heterologous Ad26/Ad5 adenovirus-vectored vaccines elicited SARS-CoV-2-specific antibody responses with potent Fc activities - Klingler, Jéromine; Kowdle, Shreyas; Bandres, Juan C.; Emami-Gorizi, Rozita; Alvarez, Raymond A.; Rao, Priyanka G.; Amanat, Fatima; Gleason, Charles; Kleiner, Giulio; Simon, Viviana; Edelstein, Alexis; Perandones, Claudia; et al. (Frontiers in Immunology, 2024)
Antibodies against the SARS-CoV-2 spike protein are a critical immune determinant for protection against the virus. While virus neutralization is a key function of spike-specific antibodies, antibodies also mediate Fc-dependent activities that can play a role in protection or pathogenesis. This study characterized serum antibody responses elicited after two doses of heterologous adenovirus-vectored (Ad26/Ad5) vaccines.Vaccine-induced antibody binding titers and Fc-mediated functions decreased over six months, while neutralization titers remained stable. Comparison of antibody isotypes elicited after Ad26/Ad5 vs. LNP-mRNA vaccination and after infection showed that anti-spike IgG1 were dominant and produced to high levels in all groups. The Ad26/Ad5 vaccines also induced IgG4 but not IgG2 and IgG3, whereas the LNP-mRNA vaccines elicited a full Ig spectrum (IgM, IgG1-4, IgA1-2). Convalescent COVID-19 patients had mainly IgM and IgA1 alongside IgG1. Despite these differences, the neutralization potencies against early variants were similar. However, both vaccine groups had antibodies with greater Fc potencies of binding complement and Fc receptors than the COVID-19 group. The Ad26/Ad5 group also displayed a greater potency of RBD-specific antibody-mediated cellular phagocytosis. Hence, antibodies with distinctive quality were induced by different vaccines and infection. The data imply the utility of different vaccine platforms to elicit antibody responses with fine-tuned Fc activities.